The Influence of Profitability and Environmental Cost on Green Accounting in Energy Sector Companies - Amelia, Mike; Fransisca, Septiani (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2025)
This study aims to analyze the influence of profitability and environmental costs on green accounting in energy sector companies. The approach used in this study is a quantitative approach with secondary data from annual reports and sustainability reports published on the companies' official websites. The population for this study consists of all energy sector companies listed on the Indonesia Stock Exchange in 2022-2023, totaling 90 companies. The sampling technique used purposive sampling, resulting in 47 companies meeting the criteria. The study period was two years, resulting in a total of 94 research samples. Data analysis was conducted using classical assumption tests, multiple linear regression tests, and hypothesis tests. The results of the tests indicated that profitability and environmental costs significantly influence green accounting